Sarcopenia as a comorbidity‐independent predictor of survival following radical cystectomy for bladder cancer. Issue 3 (25th February 2018) - Mayr, Roman; Gierth, Michael; Zeman, Florian; Reiffen, Marieke; Seeger, Philipp; Wezel, Felix; Pycha, Armin; Comploj, Evi; Bonatti, Matteo; Ritter, Manuel; van Rhijn, Bas W.G.; Burger, Maximilian; et al.
Abstract: Background: A multicentre study was conducted to investigate the impact of sarcopenia as an independent predictor of oncological outcome after radical cystectomy for bladder cancer. Methods: In total, 500 patients with available digital computed tomography scans of the abdomen obtained within 90 days before surgery were identified. The lumbar skeletal muscle index was measured using pre‐operative computed tomography. Cancer‐specific survival (CSS) and overall survival (OS) were estimated using Kaplan–Meier curves. Predictors of CSS and OS were analysed by univariable and multivariable Cox regression models. Results: Based on skeletal muscle index, 189 patients (37.8%) were classified as sarcopenic. Patients with sarcopenia were older compared with their counterparts ( P = 0.002), but both groups were comparable regarding to gender, comorbidity, tumor, node, metastasis (TNM) stage, and type of urinary diversion (all P > 0.05). In total, 234 (46.8%) patients died, and of these, 145 (29.0%) died because of urothelial carcinoma of the bladder. Sarcopenic patients had significantly worse 5 year OS (38.3% vs. 50.5%; P = 0.002) and 5 year CSS (49.5% vs. 62.3%; P = 0.016) rates compared with patients without sarcopenia. Moreover, sarcopenia was associated independently with both increased all‐cause mortality (hazard ratio, 1.43; 95% confidence interval 1.09–1.87; P = 0.01) and increased cancer‐specific mortality (hazard ratio, 1.42; 95% confidence interval, 1.00–2.02; P = 0.048). Our results are limited by the lack of prospective frailty assessment. Conclusions: Sarcopenia has been shown to be an independent predictor for OS and CSS in a large multicentre study with patients undergoing radical cystectomy for bladder cancer.